Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Augmented expression of gamma-glutamyl transferase 5 (GGT5) impairs testicular steroidogenesis by deregulating local oxidative stress - Wei Li; Zhi-qun Wu; Shun Zhang; Rui Cao; Jie Zhao; Zhi-jian Sun; Wei Zou (Cell and Tissue Research, 2016)

Paraburkholderia caffeinitolerans sp. nov., a caffeine degrading species isolated from a tea plantation soil sample - Zi-Qing Gao; Dong-Ying Zhao; Lei Xu; Rui-Ting Zhao; Ming Chen; Chun-Zhi Zhang (Antonie van Leeuwenhoek, 2016)

Complete genome sequence of a sapovirus from a child in Zhejiang, China - Xiaohong Zhou; Yi Sun; Xiaochun Shang; Jian Gao; Xueqin Zhao; Huiqun Shuai; Rui Zhang; Yanjun Zhang (Virus Genes, 2016)

Application of TiO2-organobentonite modified by cetyltrimethylammonium chloride photocatalyst and polyaluminum chloride coagulant for pretreatment of aging landfill leachate - Yi-Jie Zhang; Zhao-Hui Yang; Pei-Pei Song; Hai-Yin Xu; Rui Xu; Jing Huang; Juan Li; Yan Zhou (Environmental Science and Pollution Research, 2016)

Cardiotoxicity screening: a review of rapid-throughput in vitro approaches - Xichun Li; Rui Zhang; Bin Zhao; Christoph Lossin; Zhengyu Cao (Archives of Toxicology, 2016)

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

Two new compounds from the roots of Ilex pubescens and their cytotoxic activity - Huan Xiong; Fang Zhao; Jiayi Bi; Yang Zhang; Guiyun Zhao; Xue Chen; Yuncong Li; Rui Yan; Qiang Zhao; Hua Qiao; Guogang Zhang (Journal of Natural Medicines, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Expression Profiling of Several Gene Families Involved in Anthocyanin Biosynthesis in Apple (Malus domestica Borkh.) Skin During Fruit Development - Rui Meng; Juan Zhang; Lin An; Bohu Zhang; Xiaobing Jiang; Yazhou Yang; Zhengyang Zhao (Journal of Plant Growth Regulation, 2016)

Mutations in circularly permuted GTPase family genes AtNOA1/RIF1/SVR10 and BPG2 suppress var2-mediated leaf variegation in Arabidopsis thaliana - Yafei Qi; Jun Zhao; Rui An; Juan Zhang; Shuang Liang; Jingxia Shao; Xiayan Liu; Lijun An; Fei Yu (Photosynthesis Research, 2016)

Variation analysis of pathogenic Vibrio spp. and Pseudomonas spp. in Changhai mollusc farming waters using real-time PCR assay during 2011–2014 - Rui Liu; Limei Qiu; Xin Zhao; Huan Zhang; Lingling Wang; Zhanhui Hou; Dahai Gao; Linsheng Song (Marine Biology Research, 2016)

Breeding of an intraspecific kelp hybrid Dongfang no. 6 (Saccharina japonica, Phaeophyceae, Laminariales) for suitable processing products and evaluation of its culture performance - Xiaojie Li; Zhuangzhi Zhang; Shancun Qu; Guangjin Liang; Nan Zhao; Juan Sun; Shaofeng Song; Zengmei Cao; Xia Li; Jinhua Pan; Shiju Luo; Linan Zhang; et al. (Journal of Applied Phycology, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

First survey of parasitic helminths of goats along the Han River in Hubei Province, China - Xin Yang; Robin B. Gasser; Rui Fang; Jinrong Zeng; Kaixiang Zhu; Mingwei Qi; Zongze Zhang; Li Tan; Weiqiang Lei; Yanqin Zhou; Junlong Zhao; Min Hu (Acta Parasitologica, 2016)
Diseases caused by parasitic helminths cause considerable production and economic losses in livestock worldwide. Understanding the epidemiology of these parasites has important implications for controlling them. The main purpose of the present study was to estimate the prevalence of key parasitic helminths in goats along the Han River in Zhanggang, Hubei Province (from January to December 2014). We used faecal flotation and sedimentation techniques as well as PCR-based DNA sequencing to detect and identify helminths. Results showed that the prevalence of helminths was high throughout the year, particularly for gastrointestinal nematodes. These first findings provide useful baseline information for goat helminths in Zhanggang, and a starting point for the implementation of control programs. With an increased expansion of the goat industry in China, the findings also emphasise the need to undertake prevalence surveys in other regions of China where extensive farming practices are used.